ETS‐dependent enhancers for endothelial‐specific expression of serum/glucocorticoid‐regulated kinase 1 during mouse embryo development. (28th June 2021) - Harada, Yukihiro; Tanaka, Toru; Arai, Yuji; Isomoto, Yoshie; Nakano, Atsushi; Nakao, Shu; Urasaki, Akihiro; Watanabe, Yusuke; Kawamura, Teruhisa; Nakagawa, Osamu
Abstract: Serum/glucocorticoid‐regulated kinase 1 (SGK1) is predominantly expressed in endothelial cells of mouse embryos, and Sgk1 null mice show embryonic lethality due to impaired vascular formation. However, how the SGK1 expression is controlled in developing vasculature remains unknown. In this study, we first identified a proximal endothelial enhancer through lacZ reporter mouse analyses. The mouse Sgk1 proximal enhancer was narrowed down to the 5' region of the major transcription initiation site, while a human corresponding region possessed relatively weak activity. We then searched for distal enhancer candidates using in silico analyses of publicly available databases for DNase accessibility, RNA polymerase association and chromatin modification. A region approximately 500 kb distant from the human SGK1 gene was conserved in the mouse, and the mouse and human genomic fragments drove transcription restricted to embryonic endothelial cells. Minimal fragments of both proximal and distal enhancers had consensus binding elements for the ETS transcription factors, which were essential for the responsiveness to ERG, FLI1 and ETS1 proteins in luciferase assays and the endothelial lacZ reporter expression in mouse embryos. These results suggest that endothelial SGK1 expression in embryonic vasculature is maintained through at least two ETS‐regulated enhancers located in the proximal and distal regions. Abstract : Serum/glucocorticoid‐regulated kinase 1 (SGK1) is predominantly expressed in endothelial cells of mouse embryos, and Sgk1 null mice show embryonic lethality due to impaired vascular formation. The results in this study suggest that endothelial SGK1 expression in embryonic vasculature is maintained through at least two ETS‐regulated enhancers located in the proximal and distal regions.